Strategic Planning and Its Impact in the Application of Total Quality Requirements in University Education from the Perspective of Faculty Members at Sirte University - Mustafa Abdullah Mahmoud; Mohammad Oma Ali Shgluof (المجلة العربية لضمان جودة التعليم الجامعي, 2017)
Abstract: This paper aimed to identify the extent of the application of strategic planning among faculty members in the colleges of Sirte University. It also aimed to identify the extent of the application of TQM at colleges as seen by the faculty members. The  focus was on these areas: course descriptions, rules and regulations, educational technology, and the library. Furthermore, this paper aimed to investigate the impact of the application of the concept of strategic planning on TQM in the colleges of Sirte University. The study population consisted of all faculty members, and a sample was randomly  selected. 75 questionnaires were distributed and (58) questionnaires were returned. the Statistical Package for Social Sciences ( SPSS) was used for analyzing the collected data. Statistical procedures included frequencies, means, standard deviations, and coefficient alpha Cronbach to verify the reliability of study instruments, as well as the test of simple regression analysis to examine the impact, and the (t) test (t) per sample to measure the impact of this application on the overall quality areas. Through data analysis, the following findings were revealed. • Colleges of Sirte University applied the concept of strategic planning and requirements  of TQM under investigation  including course descriptions, rules and regulations, educational media and information technology and faculty members, where the result of  applying these requirements was  positive. • The study showed no significant differences in the faculty members’ perspective of the level of applying TQM that can be attributed to to the academic degree. • The study also showed that there was an  impact of the presence of a significant effect of the concept of strategic planning (independent variable) on the application of the  educational technology (the dependent variable).